2020
DOI: 10.1155/2020/1903734
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Diabetes Mellitus Classification from rs-fMRI Data Using Convolutional Neural Networks

Abstract: Background. As a chronic progressive disease, diabetes mellitus (DM) has a high incidence worldwide, and it impacts on cognitive and learning abilities in the lifetime even in the early stage, may degenerate memory in middle age, and perhaps increases the risk of Alzheimer’s disease. Method. In this work, we propose a convolutional neural network (CNN) based classification method to help classify diabetes by distinguishing the brains with abnormal functions from the normal ones on resting-state functional magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Some studies have reported that MRI and fMRI can clearly show the changes in the shape and size of the harness in the state of liver disease, which is of great reference value for evaluating the diagnosis of chronic liver disease and the functional reserve of the liver. The results of this study found that the sensitivity of fMRI in diagnosing benign nodular liver lesions was 83.33%, the specificity was 85.29%, the accuracy was 84.09%, and the Kappa value was 0.672, suggesting that fMRI has a certain reference value in the differential diagnosis of benign and malignant liver sarcoidosis [ 18 ]. CEUS detected 43 lesions and fMRI detected 45 lesions, and the sensitivity was higher than that of CEUS, it can be seen that fMRI can make up for the deficiency of CEUS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that MRI and fMRI can clearly show the changes in the shape and size of the harness in the state of liver disease, which is of great reference value for evaluating the diagnosis of chronic liver disease and the functional reserve of the liver. The results of this study found that the sensitivity of fMRI in diagnosing benign nodular liver lesions was 83.33%, the specificity was 85.29%, the accuracy was 84.09%, and the Kappa value was 0.672, suggesting that fMRI has a certain reference value in the differential diagnosis of benign and malignant liver sarcoidosis [ 18 ]. CEUS detected 43 lesions and fMRI detected 45 lesions, and the sensitivity was higher than that of CEUS, it can be seen that fMRI can make up for the deficiency of CEUS.…”
Section: Discussionmentioning
confidence: 99%